MR in phenylketonuria-related brain lesions - Dezortová, M; Hájek, M; Tintera, J; Hejcmanová, L; Syková, E (Acta radiologica (Stockholm, Sweden, 2001)
PURPOSE: Phenylketonuria (PKU) patients were examined by different MR techniques to explain the pathological changes observed in periventricular white brain matter using conventional MR imaging. MATERIAL AND METHODS: Fifteen patients with treated classical PKU were examined by 1H spectroscopy, relaxometry and diffusion imaging on a whole-body 1.5-T MR imager. RESULTS: Known PKU lesions characterized by T2 enhancement in periventricular white matter were observed in all patients. The MR spectra from the lesioned areas showed a significant decrease in choline concentration. The mean ADC of water decreased and tortuosity increased in PKU lesions compared to control data. CONCLUSION: The results support the following hypothesis: The T2 increase in the PKU lesion reflects a raised concentration of free water molecules (about 15%) that have an increased trajectory between collisions compared to the same region in controls. The increase in water mobility might be explained by changes in extracellular space volume and myelin sheaths, which, presumably, have a different geometry with more hydrophobic sites in PKU patients. The changes result in increased tortuosity and may be confirmed by the loss of anisotropy in PKU lesions.
Keywords: Magnetic Resonance Imaging; mozek; magnetická rezonanční tomografie; Humans; Choline; Phenylketonurias; dospělí; lidé; magnetická rezonanční spektroskopie; cholin; Brain Chemistry; Adult; difuze; mozek - chemie; Diffusion; Brain; voda; Water; Magnetic Resonance Spectroscopy; fenylketonurie